Experimental Investigation of Cigarette Butts as a Trigger on Smoldering Combustion Propagation of Peat; Case Study on Pelelawan Peat - Awaludin Martin; Yogi Wibowo Agusta; Pither Palamba (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2020)
Peatland fires are a problem every year in Indonesia especially in Sumatera Island. In Riau during the dry season, there will be peatland fires that are difficult to extinguish. There are several reasons for peatland fires and this study will analyze whether cigarette butts can cause peat fires or not. In this research peat sample was dried at 35-45°C and at temperature at 115°C to reduce water content in peat samples. Cigarette butts as a trigger were prepared with a length of 30 mm and tested on a bomb calorimeter to determine their calorific values. The cigarette butts with the highest HHV (High Heating Value) were used and burned on the surface of the peat sample by adding airflow to the sample with varying flow rates. The fastest of smoldering combustion propagation velocity was obtained 785 mm/hour for vertical direction and 1336 mm/hour for horizontal direction with speed of airflow of 5 m/s. The highest temperature was obtained in the experiment of 902°C with the speed of airflow of 5 m/s.